2015
DOI: 10.1007/s00270-015-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Outcomes Following Percutaneous Transluminal Angioplasty and Stenting in the Treatment of Transplant Renal Artery Stenosis

Abstract: Outcomes following PTA and stenting for the treatment of TRAS have been shown to be favourable. However, there is a distinct lack of well designed studies assessing outcomes following intervention. Outcome reporting may be improved by the introduction of standardised outcome measures with reporting of outcomes into a multi-centre registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 36 publications
7
79
1
1
Order By: Relevance
“…Early diagnosis and treatment of TRAS is important for prevention of graft damage and the systemic effects of hypertension. As a consequence of the developments in interventional radiology, operations including endovascular-balloon-angioplasty and stent implantation are more commonly performed treatment modalities [4,5,6,7,8]. Herein, we report an interesting case with transplant renovascular hypertension and ascites, both problems of whom resolved with a successful intervention of renal angioplasty.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Early diagnosis and treatment of TRAS is important for prevention of graft damage and the systemic effects of hypertension. As a consequence of the developments in interventional radiology, operations including endovascular-balloon-angioplasty and stent implantation are more commonly performed treatment modalities [4,5,6,7,8]. Herein, we report an interesting case with transplant renovascular hypertension and ascites, both problems of whom resolved with a successful intervention of renal angioplasty.…”
Section: Introductionmentioning
confidence: 88%
“…Nonetheless, we did not detect any signs of pulmonary oedema in clinical or radiological examination of the patient. TRAS is a vascular complication following renal transplantation, current treatment of which includes approaches of endovascular-balloon-dilation and stent implantation [2,4,7]. Salsamendi et al reported good outcome with endovascular balloon dilation on three patients with TRAS [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidities associated with TRAS include diabetes mellitus, hypertension, hyperlipidaemia and smoking 3. Proposed causes include donor or recipient artery atheroma, arterial trauma during procurement or transplantation, different suture techniques with end-to-end anastomosis being more liable to error, immune-mediated vascular damage, prolonged cold ischaemia time and rarely extrinsic mechanical compression 1.…”
Section: Descriptionmentioning
confidence: 99%
“…The recurrence rate of TRAS after PTA is very high, and the subsequent management in this setting remains elusive, with some authors advocating intervention with PTA with endovascular stenting and others recommending a more conservative approach. 13 In our center, 3-dimensional computed tomography (3DCT) reconstruction has been used for patients at high risk of TRAS. To examine the application value of 3DCT reconstruction in kidney transplant recipients, we retrospectively reviewed all cases suspicious of TRAS.…”
Section: Introductionmentioning
confidence: 99%